Evaluation of Combined Irrigation Capacity for SDI Corn Production - Rocio Reyes Esteves (Kansas Agricultural Experiment Station Research Reports, 2024)
Subsurface drip irrigation (SDI) is recognized as an efficient irrigation method that minimizes or eliminates water losses typical of sprinkler irrigation systems. Its adoption has increased in the Ogallala aquifer region. It has been reported that SDI allows reductions in irrigation by up to 25% without significant corn grain yield reduction. This corn intensification study was conducted under SDI for the 2023 growing season at the Kansas State University Northwest Research-Extension Center in Colby, KS. One corn hybrid (DeKalb DKC62-69RIB) was grown with fertilization and weed control techniques at a plant density of 28,000 plants/a using three irrigation levels (100%, 85%, and 75% of calculated well-watered ET minus rain). Average yields were 201, 200, and 198.2 bu/a for the 100%, 85%, and 75% ET minus Rain irrigation levels, respectively, indicating that irrigation does not have to increase with this crop planting arrangement when using SDI. The corn hybrid yielded well, and plant density attained good yields. Crop production under limited irrigation has been identified as a critical activity necessary to meet projected food needs in 2050. Additionally, the proposed strategies are well aligned with Ogallala aquifer conservation goals and the needs of the region’s farmers.
Keywords: corn; subsurface drip irrigation; combined irrigation capacity; Ogallala aquifer conservation